If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + -5m) + 4 = 1 + -2m (1 * -3 + -5m * -3) + 4 = 1 + -2m (-3 + 15m) + 4 = 1 + -2m Reorder the terms: -3 + 4 + 15m = 1 + -2m Combine like terms: -3 + 4 = 1 1 + 15m = 1 + -2m Add '-1' to each side of the equation. 1 + -1 + 15m = 1 + -1 + -2m Combine like terms: 1 + -1 = 0 0 + 15m = 1 + -1 + -2m 15m = 1 + -1 + -2m Combine like terms: 1 + -1 = 0 15m = 0 + -2m 15m = -2m Solving 15m = -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. 15m + 2m = -2m + 2m Combine like terms: 15m + 2m = 17m 17m = -2m + 2m Combine like terms: -2m + 2m = 0 17m = 0 Divide each side by '17'. m = 0 Simplifying m = 0
| 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 | | t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 |